Passive control for singular time-delay system with actuator saturation - Fu, Lei; Ma, Yuechao (Applied mathematics and computation, 2016)
This paper considers the problem of passivity controller design for singular time-delay system with actuator saturation and nonlinear disturbance. Firstly, by tuning the Wirtinger-based integral inequality, a sufficient condition is derived to guarantee that the nonlinear singular time-delay system is regular, impulse free, asymptotically stable with the dissipation performance. Then, based on the derived condition, and applying linear matrix inequalities(LMIs) techniques, the passive state feedback controller is synthesized. Moreover, the maximal estimate of the domain of attraction is proposed by an optimization problem. Finally, some numerical examples are given to illustrate the effectiveness of the obtained theoretic results.